2022
DOI: 10.4012/dmj.2021-065
|View full text |Cite
|
Sign up to set email alerts
|

Are resin-containing pulp capping materials as reliable as traditional ones in terms of local and systemic biological effects?

Abstract: The aim of this study was to compare the local and systemic effects of current pulp capping materials containing resin with those of traditional materials in an animal study. A total of 48 rats were used: a control group (n=12) (sub-control and negative control), a resin-containing group (n=18) (Calcimol LC, Theracal LC, Activa-BioActive Base/Liner), and a traditional group (n=18) (Biodentine, ProRoot MTA, Dycal). The materials which had been placed in polyethylene tubes were implanted in subcutaneous pockets.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 29 publications
1
8
0
Order By: Relevance
“…These results are in accordance with previous studies on several cell subpopulations (Saygili et al, 2017; Rodríguez‐Lozano et al, 2019). The resinous component in endodontic sealers or in resin‐modified calcium silicate cements has been associated with the increased cytotoxicity (Bakir et al, 2022; Sanz, Soler‐Doria, et al, 2021; Silva et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…These results are in accordance with previous studies on several cell subpopulations (Saygili et al, 2017; Rodríguez‐Lozano et al, 2019). The resinous component in endodontic sealers or in resin‐modified calcium silicate cements has been associated with the increased cytotoxicity (Bakir et al, 2022; Sanz, Soler‐Doria, et al, 2021; Silva et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Even though ACTIVA BioACTIVE supports human dental pulp stem cells’ (hDPSCs) proliferation, mineralization and attachment, further evaluation of its cytotoxicity needs to be conducted before being used for VPT [ 28 ]. Based on available research, it can be stated that, in cases of resin-containing materials, the risk of severe inflammation is higher than with CSMs; however, ACTIVA BioACTIVE-BASE/LINER showed some promising results in terms of more successful local and systemic tissue responses [ 29 ]. Literature does not provide sufficient evidence to substantiate its use in VPT; available data suggest that resin-free hydraulic calcium-silicate cements promote cell viability and bioactivity towards human cells better than resin-based agents, resulting in more successful clinical outcomes [ 30 , 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…Concerning the microbiological effect, a randomized clinical study was conducted using permanent carious molars treated with indirect capping and found that the reduction of the bacterial count in both Streptococcus mutans and Lactobacillus was using Biner LC (light-cured hydroxy calcium phosphate) or TheraCal LC [ 38 ]. Moreover, in vivo subcutaneous implantation test performed in rats showed irregular collagen formation and tissue inflammation; such study informed that inflammation in the liver and kidney tissue of the rats was more severe with the use of TheraCal LC, possibly attributable to the light-cured compounds [ 39 ].…”
Section: Discussionmentioning
confidence: 99%